2011
DOI: 10.1073/pnas.1118967109
|View full text |Cite
|
Sign up to set email alerts
|

Cultural diversification promotes rapid phenotypic evolution in Xavánte Indians

Abstract: Shifts in social structure and cultural practices can potentially promote unusual combinations of allele frequencies that drive the evolution of genetic and phenotypic novelties during human evolution. These cultural practices act in combination with geographical and linguistic barriers and can promote faster evolutionary changes shaped by gene-culture interactions. However, specific cases indicative of this interaction are scarce. Here we show that quantitative genetic parameters obtained from cephalometric d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
1
14
0
2
Order By: Relevance
“…Also, studies on phenotypic covariance structures of Neotropical primate skulls demonstrated that it have remained relatively constant, even across phyletic diversification that enabled the phenotypic means to evolve during the last 30 million years (Marriog and Cheverud, ). A similar result was obtained in human populations, where covariance has also been shown to be stable (González‐José et al, , Hünemeier et al, ), even under extreme mechanical stressors experienced during early postnatal phases, as is the case of intentionally deformed skulls (Martínez‐Abadías et al, ).…”
Section: Discussionsupporting
confidence: 66%
“…Also, studies on phenotypic covariance structures of Neotropical primate skulls demonstrated that it have remained relatively constant, even across phyletic diversification that enabled the phenotypic means to evolve during the last 30 million years (Marriog and Cheverud, ). A similar result was obtained in human populations, where covariance has also been shown to be stable (González‐José et al, , Hünemeier et al, ), even under extreme mechanical stressors experienced during early postnatal phases, as is the case of intentionally deformed skulls (Martínez‐Abadías et al, ).…”
Section: Discussionsupporting
confidence: 66%
“…If powerful men could marry more than one woman, and preferably sisters, all their children would share the same mitochondrial lineage, whose frequency could significantly increase. Additionally, cultural practices like those mentioned above have prevented fusion between the Xavante and the other Je populations located in the Brazilian Central Plateau, such as the Kayapó (Hünemeier et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary scholarship in this domain includes investigations of geneculture interaction on the rate of evolution (Hünemeier et al 2012), the role of gene-culture interactions in geographically-restricted adaptation over the last 50,000 years (Laland et al 2010), gene-behavior coevolution in the case of the origins of language (Aoki 2001), the evolution of social norms (Gintis 2003) and the global, early-Holocene experiments with plant and animal domestication. In a recent work on the European Neolithic (Zeder 2008), it has been noted that multiple taxa were significantly coevolving.…”
Section: Mutualisms: Gene-culture Coevolutionmentioning
confidence: 99%